Programa de entrenamiento a padres de niños con discapacidad auditiva: Cómo abordar el desarrollo del lenguaje en infantes con implante coclear (IC) durante la primera infancia. - Rodríguez Montoya, Silvia Raquel (Universidad Antonio Nariño, 2023)
The article presents the design and implementation of a training and empowerment program for parents, for the development of language in children with hearing impairment who are users of cochlear implants during early childhood. The program is the result of systematization in a pedagogical model of twenty years of clinical practice, the implementation is presented through a case study carried out for six months in three cohorts; an initial intervention and two individual trainings for a week for a total of 36 sessions. For the analysis of the data, standardized tests, questionnaires for validated parents in Spanish for the population with hearing impairment, direct observation and video recordings of the communicative interactions promoted by the parents' verbalizations from the semantic and syntactic component of the language were used. They were categorized in a database for analysis.